Routine Reporting of Environmental Risk: The First Traces of Micropollutants in the German Press. Issue 8 (17th November 2019) - Schulte-Römer, Nona; Söding, Max
ABSTRACT: This article analyzes the emergence of a new environmental issue in the German press. Since the 1990s, scientists have detected traces of pharmaceuticals, hormones and chemicals in all segments of the water cycle. These micropollutants have negative effects on aquatic life and might affect human health. Their sources are manifold and include private households. Yet although micropollutants of are direct concern to media audiences, they are a challenging topic for news reporting. Although this issue is systemic and fraught with uncertainty, it does not easily translate into news stories. Our content analysis of 444 articles (1995–2015) reveals that the societal risk was rarely presented as a stand-alone topic. Instead, the issue was mostly covered as part of local routine reporting and framed as a challenge for experts to solve. Over time, the reporting became more managerial, while media framings of micropollutants gained more substance and scope. We contend that local routine reporting should receive more attention as a public forum for addressing emerging environmental concerns.